KINEMATIC METHOD OF CALCULATING THE VALUES OF MOMENTS IN THE MOST DANGEROUS SECTIONS OF BEAMS - Pavlikov, A.; Prykhodko, Y. (Academic journal Industrial Machine Building Civil Engineering, 2017)
The method of applying technique of the kinematic limit equilibrium method was given. Formulas for calculating the values of the bending moments for reinforced concrete structures and their advantages over conventional static method, which is based on the equations of equilibrium was also derived. In this article there is shown how this method is used for the most widely-spread reinforced concrete elements in the building industry which have a great deal with bending. The simply supported beams are mostly used as such elements. They are with position fixed ends in this article. There are three kinds of loads for above mentioned beams: by one concentrated force within limits of the beam, by the uniform load over the full span and by two concentrated forces which are pointed symmetrically about the central axe of the beam and spaced at certain intervals apart. Keywords: the kinematic method, the limit equilibrium method, the virtual work, the plastic hinge, the bending moment.